การเตรียมตัวโคบอลต์บนเส้นใยนาโนซิลิกา-อะลูมินาโดยอิเล็กโทรสปินนิงสำหรับการสังเคราะห์ฟิสเชอร์-ทรอปช์ - นรรฏธวรรณ ถกลเกียรติกุล (จุฬาลงกรณ์มหาวิทยาลัย, 2012)
Co/SiO₂-Al₂O₃ fiber catalysts for Fischer-Tropsch synthesis were prepared by electrospinning techniques and impregnation method. The fibers were prepared by varying 1, 2, 3, 4 and 5% by weight of alumina. The optimum condition for prepared Co/SiO₂-Al₂O₃ fiber, needle size of 0.40 mm, applied voltage of 15 kV and tip-to-collector distance (TCD) of 15 cm. The average diameter of fiber increased with increasing alumina content. For Co/SiO₂-Al₂O₃ fiber catalysts were prepared by impregnating a solution of cobalt nitrate at different metal loading (10, 15, and 20%wt) followed by calcined at 400 ℃ and characterized by SEM/EDS, TEM, BET, XRD, and TPR compared with the porous Co/SiO₂ catalyst. The results showed that the fiber catalysts could be reduced easier than the porous catalyst. The catalyst performance test for Fischer-Tropsch synthesis showed that the porous catalyst were higher CO conversion and lower CH₄ selectivity than the fiber catalyst because the porous catalyst high water gas shift. The Co/SiO₂-Al₂O₃ fiber catalyst exhibited the highest of CO conversion of 56.37% with CH₄ selectivity of 95.04%. For CO conversion of the fiber catalyst at different cobalt content showed that CO conversion increased with increasing cobalt content.